2011
DOI: 10.1186/cc10464
|View full text |Cite
|
Sign up to set email alerts
|

Serial increase of IL-12 response and human leukocyte antigen-DR expression in severe sepsis survivors

Abstract: IntroductionSepsis-induced immunosuppression may result in death. The mechanisms of immune suppression include loss of macrophage and monocyte expression of the major histocompatibility complex, increased anti-inflammatory cytokine expression and decreased expression of proinflammatory cytokines. In this study, we sought to determine the mechanisms of immune suppression in severe sepsis by repeated detection.MethodsWe designed this prospective observational study to measure monocyte human leukocyte antigen (HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
3
30
0
1
Order By: Relevance
“…Perhaps Nascimento et al’s research investigated the role of T reg cells in the immune response to secondary infection and our study analyzed a primary infection. Plasma IL-6 level in survivors with severe sepsis was lower than that in non-survivors [19, 20]. In this work, total T reg cells in survivors were higher.…”
Section: Discussionmentioning
confidence: 56%
“…Perhaps Nascimento et al’s research investigated the role of T reg cells in the immune response to secondary infection and our study analyzed a primary infection. Plasma IL-6 level in survivors with severe sepsis was lower than that in non-survivors [19, 20]. In this work, total T reg cells in survivors were higher.…”
Section: Discussionmentioning
confidence: 56%
“…It has also been found that peripheral monocytes isolated from septic humans and mice produce less IL-12 in response to stimulation ex vivo with TLR ligands than those from healthy controls, yet cells from patients that survive sepsis produce greater amounts of IL-12 than those from nonsurvivors. In contrast, levels of IL-10 are elevated in nonsurvivors relative to survivors (113,359,439). In both experimental models and patients with sepsis, APCs demonstrate decreased capacity to stimulate the T-cell proliferative response compared with healthy controls (113,227,246).…”
Section: Antigen Presentation and The Cellular Responsementioning
confidence: 68%
“…Monocytes isolated from animal models and patients with sepsis release lower amounts of proinflammatory cytokines when stimulated with Toll-like receptor ligands, suggesting that their capacity to sense and respond to new infections is impaired (6,112,220,257). In septic humans, the expression of HLA-DR is markedly decreased (174,257); however, sur- vivors demonstrate a significant recovery of HLA-DR expression compared with nonsurvivors (247,248,439). It has also been found that peripheral monocytes isolated from septic humans and mice produce less IL-12 in response to stimulation ex vivo with TLR ligands than those from healthy controls, yet cells from patients that survive sepsis produce greater amounts of IL-12 than those from nonsurvivors.…”
Section: Antigen Presentation and The Cellular Responsementioning
confidence: 90%
“…Clinically, a prospective study in patients undergoing major visceral surgery suggested that a selective defect in preoperative monocyte IL-12 production impairs the host defense against postoperative infections and, thus, increases the risk of lethal sepsis [148]. Likewise, it was reported that survivors from severe sepsis produce more IL-12 from LPS-stimulated peripheral blood mononuclear cells (PBMCs) than nonsurvivors [149], and that they show serial increases in their IL-12 response from PBMCs [150]. …”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%